Private Sector Contribution in Achieving the Sustainable Development Goals (SDGs) 7 in Kendari, Indonesia - Faturachman Alputra Sudirman; Rahim Rifai (International Journal of Qualitative Research, 2021)
This study aims to explain and find out how the contribution of PT DSSP Power Kendari in achieving sustainable development goals (SDGs) 7 (clean and affordable energy) through cooperation between PT DSSP Power Kendari and State Electricity Company (PLN). This study uses a qualitative approach and type of descriptive research with data collection techniques through interviews and documentation. This study uses the theory of sustainable development using the concept of Public-Private Partnership (PPP). The results of the study show that the contribution of PT DSSP Power Kendari in achieving SDGs 7 is to collaborate with PLN with a contract period of 25 years, to provide electricity with a capacity of 2 x 50 megawatts and create electricity education programs for the younger generation, this contribution is made to achieve development sustainable electrical energy by discovering the use of household electricity in the city of Kendari.